Mental health apps in India: regulatory landscape and future directions - M. I. Singh Sethi; Rakesh C. Kumar; Narayana Manjunatha; Channaveerachari Naveen Kumar; Suresh Bada Math (BJPsych International)
Mental health apps (MHAs) are increasingly popular in India due to rising mental health awareness and app accessibility. Despite their benefits, like mood tracking, sleep tools and virtual therapy, MHAs lack regulatory oversight. India's framework, including the Central Drugs Standard Control Organization (CDSCO) and Medical Device Rules 2017, does not cover standalone health apps, raising concerns about data privacy and accuracy. Establishing a centralised regulatory body with guidelines for MHAs is essential for user safety and efficacy. This paper examines the current regulatory landscape, compares international approaches and proposes a tiered regulatory framework to foster responsible innovation while safeguarding user interests in digital mental health services.